Artemisinin–(Iso)quinoline Hybrids by C−H Activation and Click Chemistry: Combating Multidrug-Resistant Malaria - Çapcı, Aysun; Lorion, Mélanie M.; Wang, Hui; Simon, Nina; Leidenberger, Maria; Borges Silva, Mariana C.; Moreira, Diogo R.M.; Zhu, Yongping; Meng, Yuqing; Chen, Jia Yun; Lee, Yew Mun; Friedrich, Oliver; et al. (Angewandte Chemie International Edition, 2019)
A substantial challenge worldwide is emergent drug resistance in malaria parasites against approved drugs, such as chloroquine (CQ). To address these unsolved CQ resistance issues, only rare examples of artemisinin (ART)-based hybrids have been reported. Moreover, protein targets of such hybrids have not been identified yet, and the reason for the superior efficacy of these hybrids is still not known. Herein, we report the synthesis of novel ART–isoquinoline and ART–quinoline hybrids showing highly improved potencies against CQ-resistant and multidrug-resistant P. falciparum strains (EC50 (Dd2) down to 1.0 nm; EC50 (K1) down to 0.78 nm) compared to CQ (EC50 (Dd2)=165.3 nm; EC50 (K1)=302.8 nm) and strongly suppressing parasitemia in experimental malaria. These new compounds are easily accessible by step-economic C−H activation and copper(I)-catalyzed azide–alkyne cycloaddition (CuAAC) click reactions. Through chemical proteomics, putatively hybrid-binding protein targets of the ART-quinolines were successfully identified in addition to known targets of quinoline and artemisinin alone, suggesting that the hybrids act through multiple modes of action to overcome resistance.
CRIS-Team Scopus Importer:2019-08-27
Keywords: antimalarial agents; artemisinin; drug resistance; hybridization; proteomics

Green I-Based Fluorescence Assay to Assess Cell Viability of Malaria Parasites for Routine Use in Compound Screening. - Leidenberger, Maria; Voigtländer, Cornelia; Simon, Nina; Kappes, Bärbel (Methods in Molecular Biology, 2017)
Green I-based fluorescence assay protocol to be used for routine screening of compounds and extracts in a research laboratory environment. A variation of the standard protocol is also provided allowing to address stage-specific effects of fast-acting drugs.
Keywords: Fluorescence assay; SYBR Green; Growth inhibition assay; Malaria; Plasmodium falciparum; Compound screening

Improved stability of polyclonal antibodies: A case study with lyophilization-conserved antibodies raised against epitopes from the malaria parasite Plasmodium falciparum - Simon, Nina; Sperber, Christine; Voigtländer, Cornelia; Born, Julia; Gilbert, Daniel; Seyferth, Stefan; Lee, Geoffrey; Kappes, Bärbel; Friedrich, Oliver (European Journal of Pharmaceutical Sciences, 2020)
Antibodies can be produced as polyclonal (pAb) or monoclonal (mAb) liquid formulations with limited shelf-life. For pAbs, unlike mAbs, only little is known about excipients and lyophilization affecting antibody stability upon reconstitution. We used a model pAb directed against Plasmodium falciparum (Pf) pyridoxal 5′-phosphate synthase 2 (Pdx2) to systemically study effects of bulking agents (amino acids, phosphate buffers, salt solutions), sugar(alcohols), surfactants and protein additions (bovine serum albumin, BSA) in liquid pAb formulations (isolated or in combinations) on the activity to detect the antigen in Pf extracts by Western blots. Repeated freeze-thaw cycles (20x) and extended room temperature storage markedly compromised pAb stability, the former being ameliorated by addition of cryoprotectants (glycerol, sucrose). Lyophilization of pure liquid pAb formulation markedly decreased antibody reactivity upon reconstitution which was not preserved by most bulking agents tested (e.g., histidine, arginine, acetate). Among the tested salt solutions (NaCl, Ringer, PBS), phosphate buffered saline had the largest lyoprotective potential, alongside sucrose, but not trehalose or maltitol. Among combinations of excipients, PBS, sucrose, low concentration BSA and Tween potently preserved PfPdx2 stability. Results for PBS were transferable to PfEnolase pAb, indicating that some of the formulations investigated here might be a low-cost solution for more general applicability to pAbs.
CRIS-Team Scopus Importer:2019-11-15

PfMDR1 Transport Rates Assessed in Intact Isolated Plasmodium falciparum Digestive Vacuoles Reflect Functional Drug Resistance Relationship with pfmdr1 Mutations - Simon, Nina; Voigtländer, Cornelia; Kappes, Bärbel; Rohrbach, Petra; Friedrich, Oliver (Pharmaceuticals, 2022)
Drug resistance often emerges from mutations in solute transporters. Single amino acid exchanges may alter functionality of transporters with ‘de novo’ ability to transport drugs away from their site of action. The PfMDR1 transporter (or P-glycoprotein 1) is located in the membrane of the digestive vacuole (DV), functions as an ATP-dependent pump, and transports substrates into the DV. In this study, four strains of Plasmodium falciparum, carrying various pfmdr1 gene mutations, were analysed for their transport characteristics of Fluo-4 in isolated DVs of parasites. To obtain quantitative estimates for PfMDR1 DV surface expression, PfMDR1 protein amounts on each strain’s DV membrane were evaluated by quantitative ELISA. Fluo-4, acting as a substrate for PfMDR1, was applied in DV uptake assays (‘reverse Ca2+ imaging’). Viable DVs were isolated from trophozoite stages with preserved PfMDR1 activity. This newly developed assay enabled us to measure the number of Fluo-4 molecules actively transported into isolated DVs per PfMDR1 molecule. The drug-resistant strain Dd2 presented the highest transport rates, followed by K1 and the drug-sensitive strain 3D7, compatible with their copy numbers. With this assay, an evaluation of the probability of resistance formation for newly developed drugs can be implemented in early stages of drug development.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Drug resistance; Fluo-4; P-glycoprotein 1; PfMDR1; Plasmodium falciparum; Transport protein

Quantification of human complement factor H binding to asexual malaria blood stages by an enzyme-linked immunosorbent assay - Simon, Nina; Friedrich, Oliver; Kappes, Bärbel (Vaccine, 2018)
Keywords: Complement system; ELISA validation; Asexual blood stages; Surface binding; Human factor H; Malaria